2016
DOI: 10.1186/s13023-016-0481-4
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphometry in Pontocerebellar Hypoplasia type 2

Abstract: BackgroundPontocerebellar hypoplasia type 2 (PCH2) is caused by a defect in the TSEN54-gene and leads to severe and early disruption of brain development, especially of cerebellum and pons. The aim of this work was to quantify the infra- and supratentorial brain growth during postnatal brain development in children with PCH2.MethodsMRI data of 24 children with PCH2 (age 0.02–17 years., 13 females) were analysed volumetrically and compared to images of 24 typically developing age- and gender-matched children. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The same situation might be in many other countries. Despite the neurodegenerative character of the disease and only slight increase in volume of infratentorial structures postnatally, very few patients demonstrate regression in their developmental milestones ( 20 ). The absence of regression in our cases supports the hypothesis of Sánchez-Albisua et al, that there is an early onset degeneration which thereafter stabilizes, so that patients could achieve some developmental progress ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same situation might be in many other countries. Despite the neurodegenerative character of the disease and only slight increase in volume of infratentorial structures postnatally, very few patients demonstrate regression in their developmental milestones ( 20 ). The absence of regression in our cases supports the hypothesis of Sánchez-Albisua et al, that there is an early onset degeneration which thereafter stabilizes, so that patients could achieve some developmental progress ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that the progressive microcephaly in PCH2A does not result from atrophy but from reduced cerebral growth as a secondary effect of the severe cerebellar hypoplasia. 21 In support of this hypothesis, Ekert et al observed growth of the supratentorial brain in the first years of life in children with PCH2A, although the increase in volume was reduced to that observed in controls. 21 However, previous neuropathology studies in PCH2A reported atrophic and neurodegenerative features in the neocortex.…”
Section: Discussionmentioning
confidence: 89%
“…This allowed further development of clinically important biomarkers such as brain and lesion volume for longitudinal MS studies ( Brex et al., 2002 , De Stefano et al., 2014 , Sailer et al., 1999 ) – information which, currently, cannot be readily extracted from scans dating back to the 80's and early 90's if they are only available as printed films. The original, digital data is often lost or cannot be recovered due to hardware and software obsolescence issues which has also been shown in more recent studies on brain morphometry where original MR films were digitised anew and manually processed to allow for further quantification ( Ekert et al., 2016 ). In other words, especially for longitudinal studies dating back to the 80's, a decade or more of valuable image data information may not be readily accessible to modern image processing techniques which could add to the understanding of long-term pathological or morphological evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of reconstructing volumetric representations from printed MR films, however, only one single stack of past thick-slice acquisitions in a single, axial plane is captured. The slice thickness of past acquisitions can range from 5 mm like in Brex et al., 2002 , Ekert et al., 2016 , Miller et al., 1989 , Sailer et al., 1999 to 10 mm as in Brex et al., 2002 , Miller et al., 1989 , Sailer et al., 1999 to even encountered 12 mm. Hence, even in the 5 mm slice thickness case, which is the focus of this work, neighbouring slices correspond to relatively distant anatomical positions which renders purely intra-stack alignment-based motion correction approaches particularly difficult so as to recover the correct inter-slice relationship and, thus, the patient-specific anatomy.…”
Section: Introductionmentioning
confidence: 99%